A Biomimetic Composite from Solution Self‐Assembly of Chitin Nanofibers in a Silk Fibroin Matrix. (21st June 2013) - Jin, Jungho; Hassanzadeh, Pegah; Perotto, Giovanni; Sun, Wei; Brenckle, Mark A.; Kaplan, David; Omenetto, Fiorenzo G.; Rolandi, Marco
<x xml:space="preserve">Abstract</x> A chitin nanofiber‐silk biomimetic nanocomposite with enhanced mechanical properties is self‐assembled from solution to yield ultrafine chitin nanofibers embedded in a silk matrix. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>